Linking Dietary Patterns to Environmental Degradation: The Spatiotemporal Analysis of Rural Food Nitrogen Footprints in China - Xian, Chao-Fan; Gong, Cheng; Lu, Fei; Zhang, Lu; Ouyang, Zhi-Yun (Frontiers in Nutrition, 2021)
Background: China is a large emerging economy that illustrates how dietary patterns can affect food-source nitrogen (N) cycling. The indicator of food nitrogen footprint (NF) reflects the amount of reactive nitrogen (Nr) emissions and their impacts on the environment. It is a result of food production and consumption to satisfy the basic dietary demands of a given population. Different from urban food consumption with improved waste treatment, rural food consumption significantly affects the environment from food production to wastage disposal. We therefore performed a nationwide case study to link dietary patterns to environmental degradation based on rural food NF accounting. Methods: The N-Calculator model was adopted to reveal the spatiotemporal characteristics of food NFs per capita, and the regional food NFs related to China’s rural diets from 2000 to 2019. Then the food-source Nr emissions to regional environment were quantified based on the food NFs accounting and relevant inventory of regional Nr emissions. Results: (i) The average annual food NF per-capita in rural regions was lower than its national counterpart, but exhibited regional differences, mainly attributed to the dietary role of cereals. (ii) There exited significant spatiotemporal characteristics among regional food NFs that were mainly contributed by plant-derived food consumptions (73%). Sichuan, Henan, Shandong and Hunan exhibited larger regional food NFs, and the NFs growths were shown in Beijing, Shanghai and Tibet – the rural diets of which were dominated by animal-derived food. (iii) Rural diets affected the environment by the pathways of ammonia and nitrous oxide volatilizations, as well as Nr loss to water, respectively accounting for average 33%, 5% and 62% of food NFs across regions. (iv) Although current rural dietary patterns still relied on cereal and vegetable consumptions, more animal-derived food would be consumed as urbanization continues, especially in developed regions, posting a barrier for further reduction in the national food NF. Conclusion: The findings of this study highlight the importance of changing dietary patterns to the human health-environment dilemma. Strategies including the improvements in the N recycling rates, adjustments in dietary patterns, and reductions in food wastes could mitigate regional N pollutions with rural dietary shifts.